Preferensi Konsumen terhadap Pembelian Produk Organik di Kota Bandar Lampung - Tri Pujiana; Anna Dwi Putri; Dwi Arianti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze consumer preferences for purchasing organic products in Bandar Lampung City. With increasing awareness of the importance of a healthy lifestyle and environmental sustainability, organic products are increasingly popular among consumers. This study uses a quantitative approach with a survey method to collect data from consumers who purchase organic products in various markets and shops in Bandar Lampung City from November to December 2024. The variables analyzed include factors that influence purchasing decisions, namely age, education level, gender, frequency and location of purchase, and sources of information about organic products. The results show that consumers of organic products are aged between 18-56 years, with the majority being female and from those with higher education (bachelor and postgraduate). Consumers prefer organic products because of health considerations and better quality compared to conventional products. However, higher prices and product availability are inhibiting factors in purchasing organic products. This study provides important insights for organic product producers and marketers in designing more effective marketing strategies, as well as contributing to the development of the organic product market in Bandar Lampung City.